Pengembangan Media Pembelajaran Interaktif berbasis Digital untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas IV di SD Inpres Bertingkat Oebobo II, Kota Kupang - Natalia Messakh; Markus Sampe; Rista Apriliya Devi (ARZUSIN, 2025)
This study was motivated by the low learning interest among fourth-grade students in Indonesian language classes at SD Inpres Bertingkat Oebobo II, Kota Kupang. The objective of the research was to develop a valid and practical digital-based interactive learning media and to evaluate its effectiveness in enhancing students’ learning interest. The study employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The developed product was an interactive PowerPoint learning media, which was then validated and assessed for feasibility. The research subjects were fourth-grade students, and data were collected through observation, interviews, expert validation, pre-test and post-test assessments, as well as student response and interest questionnaires. Validation results from media and content experts showed a validity percentage of 92%, categorized as "Highly Valid," and the media was deemed practical for use. The average pre-test and post-test scores indicated improved learning outcomes, with an effectiveness rate of 62%, classified as "Moderately Effective." Student response and interest questionnaire results reached 77% and 79%, respectively, both falling into the "Effective" category. The study concludes that the developed interactive PowerPoint media is valid, practical, and effective in increasing students' interest in learning Indonesian language in fourth grade. The implication is that this media can serve as an innovative alternative to support a more engaging and interactive learning process.